Pang Bas : a Musical Activity of Rindu Nada Bamboo Instrumental Group - Arqam, Muh.; Florentinus, Totok Sumaryanto; Utomo, Udi (Catharsis, 2018)
This research reveals Pang Bas as a musical activity in the context of social exchange in Rindu Nada bamboo instrumental group in Sumillan village, Alla district, Enrekang regency. The research was made to analyze Pang Bas of Rindu Nada group. It used interdisciplinary approach, involving the disciplines of sociology under the paradigm of social behavior. The researcher employed qualitative research method to conduct the research. The data of this research were collected from observation, interview, and documentation. Then, the data were analyzed in data reduction, data presentation, and verification or conclusion. The findings showed that Pang Bas musical activity of Rindu Nada occurred during the rehearsal and stage performance collaborating with external parties. The activity initiated the social exchange causing aggression, praises, leadership, deprivation, and boredom towards Pang Bas. Meanwhile, during the play, Pang Bas generated social interaction to outsiders as intrinsic rewards, such as friendship, satisfaction, and social status. The extrinsic reward of it was a material thing in return. There was also a stimuli of generalization in the next meeting and discrimination prior to the success of past performance.